2016
DOI: 10.1038/ncomms10682
|View full text |Cite
|
Sign up to set email alerts
|

Shisa6 traps AMPA receptors at postsynaptic sites and prevents their desensitization during synaptic activity

Abstract: Trafficking and biophysical properties of AMPA receptors (AMPARs) in the brain depend on interactions with associated proteins. We identify Shisa6, a single transmembrane protein, as a stable and directly interacting bona fide AMPAR auxiliary subunit. Shisa6 is enriched at hippocampal postsynaptic membranes and co-localizes with AMPARs. The Shisa6 C-terminus harbours a PDZ domain ligand that binds to PSD-95, constraining mobility of AMPARs in the plasma membrane and confining them to postsynaptic densities. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
150
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(170 citation statements)
references
References 39 publications
15
150
1
Order By: Relevance
“…However, the molecular functions of SHISA6 are relatively unclear; a recent report showed that SHISA6 stabilized the AMPA receptor expression in the mouse brain, similar to SHISA9 (Klaassen et al., 2016, von Engelhardt et al., 2010). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the molecular functions of SHISA6 are relatively unclear; a recent report showed that SHISA6 stabilized the AMPA receptor expression in the mouse brain, similar to SHISA9 (Klaassen et al., 2016, von Engelhardt et al., 2010). …”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, SHISA6 has been recently reported to desensitize AMPA receptor in the CNS (Klaassen et al., 2016). SHISA6 is, therefore, a context-dependent dual functional protein.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor distribution is likely established and adjusted by diverse mechanisms. Critically, AMPARs can be mobile within the PSD, but the diffusion rate and fraction which is mobile are affected not only by binding of auxiliary subunits [33, [34, [35], but also by synaptic activity [36] and receptor desensitization [37]. Recent work makes clear that the extraordinarily high density of protein within the PSD has profound consequences for receptor mobility.…”
Section: Alignment-mediated Plasticity Arising From Postsynaptic Reormentioning
confidence: 99%
“…The physiological importance of modulation is likely to be the specialization of particular codes of short-term plasticity, in the hippocampus and cerebellum at least (von Engelhardt et al, 2010;Klaassen et al, 2016;Khodosevich et al, 2014;Devi et al, 2016). Recently, antagonists of AMPA receptors that target GluA2-g8 complexes were described (Maher et al, 2016;Kato et al, 2016), further enhancing interest in the molecular basis of complexes of GluA subunits and their auxiliary proteins as potential drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…Since the identification of the protein Stargazin, also known as g2, as the prototype transmembrane AMPA receptor regulatory protein (TARP) (Chen et al, 2000), several families of auxiliary proteins for the AMPA receptor have been described that include TARPs (Schwenk et al, 2012;Tomita et al, 2003), cornichons (Schwenk et al, 2009), GSG1L (Shanks et al, 2012) and CKAMPs (von Engelhardt et al, 2010;Klaassen et al, 2016). These proteins play an essential role in tethering AMPA-type glutamate receptors at the synapse, and also exert complex control over surface expression of functional receptors (Dakoji et al, 2003;Yamazaki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%